Oral nitrate supplementation to enhance pulmonary rehabilitation in COPD: ON-EPIC a multicentre, double-blind, placebo-controlled, randomised parallel group study. Issue 7 (6th May 2020) - Pavitt, Matthew J; Tanner, Rebecca Jayne; Lewis, Adam; Buttery, Sara; Mehta, Bhavin; Jefford, Helen; Curtis, Katrina J; Banya, Winston A S; Husain, Syed; Satkunam, Karnan; Shrikrishna, Dinesh; Man, William; et al.
Abstract : Rationale: Dietary nitrate supplementation has been proposed as a strategy to improve exercise performance, both in healthy individuals and in people with COPD. We aimed to assess whether it could enhance the effect of pulmonary rehabilitation (PR) in COPD. Methods: This double-blind, placebo-controlled, parallel group, randomised controlled study performed at four UK centres, enrolled adults with Global Initiative for Chronic Obstructive Lung Disease grade II–IV COPD and Medical Research Council dyspnoea score 3–5 or functional limitation to undertake a twice weekly 8-week PR programme. They were randomly assigned (1:1) to either 140 mL of nitrate-rich beetroot juice (BRJ) (12.9 mmol nitrate), or placebo nitrate-deplete BRJ, consumed 3 hours prior to undertaking each PR session. Allocation used computer-generated block randomisation. Measurements: The primary outcome was change in incremental shuttle walk test (ISWT) distance. Secondary outcomes included quality of life, physical activity level, endothelial function via flow-mediated dilatation, fat-free mass index and blood pressure parameters. Results: 165 participants were recruited, 78 randomised to nitrate-rich BRJ and 87 randomised to placebo. Exercise capacity increased more with active treatment (n=57) than placebo (n=65); median (IQR) change in ISWT distance +60 m (10, 85) vs +30 m (0, 70), estimated treatment effect 30 m (95% CI 10 to 40); p=0.027. Active treatment also impacted on systolic blood pressure: treatment group −5.0 mm Hg (−5.0, –3.0) versus control +6.0 mm Hg (−1.0, 15.5), estimated treatment effect −7 mm Hg (95% CI 7 to −20) (p<0.0005). No significant serious adverse events or side effects were reported. Conclusions: Dietary nitrate supplementation appears to be a well-tolerated and effective strategy to augment the benefits of PR in COPD. Trial registration number: ISRCTN27860457 .